An update of the recombinant protein expression systems of Cyanovirin-N and challenges of preclinical development - Lotfi, Hajie (Bioimpacts, 2018)
[Image: see text] Introduction: Human immunodeficiency virus (HIV) is a debilitating challenge and concern worldwide. Accessibility to highly active antiretroviral drugs is little or none for developing countries. Production of cost-effective microbicides to prevent the infection with HIV is a requirement. Cyanovirin-N (CVN) is known as a promising cyanobacterial lectin, capable of inhibiting the HIV cell entry in a highly specific manner. Methods: This review article presents an overview of attempts conducted on different expression systems for the recombinant production of CVN. We have also assessed the potential of the final recombinant product, as an effective anti-HIV microbicide, comparing prokaryotic and eukaryotic expression systems. Results: Artificial production of CVN is a challenging task because the desirable anti-HIV activity (CVN-gp120 interaction) depends on the correct formation of disulfide bonds during recombinant production. Thus, inexpensive and functional production of rCVN requires an effective expression system which must be found among the bacteria, yeast, and transgenic plants, for the subsequent satisfying medical application. Moreover, the strong anti-HIV potential of CVN in trace concentrations (micromolar to picomolar) was reported for the in vitro and in vivo tests. Conclusion: To produce pharmaceutically effective CVN, we first need to identify the best expression system, with Escherichia coli, Pichia pastoris , Lactic acid bacteria and transgenic plants being possible candidates. For this reason, heterologous production of this valuable protein is a serious challenge. Since different obstacles influence clinical trials on microbicides in the field of HIV prevention, these items should be considered for evaluating the CVN activity in pre-clinical and clinical studies.